Evaluasi Kebijakan Pembiayaan Kesehatan Bagi Masyarakat Miskin Pada Program JKN - Nadya Salsabila; Prasetio Hadi; Siti Humaira Syarif; Novita Dwi Istanti (Institut Nalanda, 2023)
The National Health Insurance Program is a government program whose purpose is to offer everyone the certainty of comprehensive health insurance and support the Indonesian people to live healthy, productive and prosperous lives. JKN must be able to provide comprehensive services and provide health financing based on equity to create cross-responsibility support between the population and the region.The method used in the preparation of this article is Literature Review, Based on the results of the study shows that health insurance in the form of Askeskin has succeeded in reaching the poor and National Health Insurance which has proven effective in several cities in Indonesia and social health insurance or Social Health Insurance (JKN) is needed. Because social health insurance provides comprehensive benefits with affordable premiums. provides a positive impact on society, including in East Kalimantan Province. Meanwhile, to observe a positive impact on the subsidized and dues group, the greater effect on the dues group shows the potential for adverse selection effects among the many affluent populations.